Method Development For The Determination Of Sulphonamide Residues In Chicken By Liquid Chromatography Ion Trap Tandem Mass Spectrometry - Ahmad, Sidek (2006)
Satu kaedah yang mudah, sensitif dan dipercayai untuk penentuan sisa lima sulfonamida